Реинжиниринг бизнес процессов в коммерческом банке (Путеводитель предпринимателя, 2020)
Reengineering of business processes in a commercial bank.The article deals with the basic premise of reengineering business processes in banking, as well as stages, forms of implementation and use of tools of reengineering.